EFL Teachers' Efforts in Developing Their Pedagogical Competence - Wulan Mayang Sari; Amalia Hasanah; Eka Sartika (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
The aims of this study were to find out investigate what EFL teachers do to developing their pedagogical competence in teaching implementation. The participants of this study were English teachers in SMP Xaverius 3 Palembang. Qualitative method was used in this study. The data gained from interview was analyzed by using thematic analysis. The study applied purposive sampling. The result of the study showed that the English teachers join some activities and programs as the efforts of developing their pedagogical competence. To increase the knowledge of classroom management, teachers usually did induction programs. Teachers also should join many kind of seminars, workshops, short courses or teacher trainings related to teaching in order to develop their knowledge of teaching methods. Teachers can develop their knowledge of classroom assessment by joining seminars, workshop, reading books or articles, watching youtube, and using other platforms. Lesson study activities are used by teachers to help them making lesson plan.